BRAND INTERACTION AND INTIMACY AS MEDIATORS BETWEEN STAY EXPERIENCE AND BRAND EVANGELISM AT MAHAVIRA HOTEL NABIRE - Nikita Felicia Agatha; Asriah Syam (RADJA PUBLIKA, 2026)
The post-pandemic recovery of the hotel industry has intensified competition and increased the importance of customer advocacy. This study examines the effect of stay experience on brand evangelism and tests the parallel mediating roles of brand interaction and brand intimacy among customers of Mahavira Hotel Nabire. A quantitative survey was conducted with 210 customers selected through purposive sampling, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings show that stay experience has positive and significant effects on brand interaction and brand intimacy. Brand intimacy significantly influences brand evangelism, whereas stay experience and brand interaction do not have significant direct effects on brand evangelism. Brand intimacy significantly mediates the relationship between stay experience and brand evangelism, while brand interaction does not. These results indicate that positive hotel experiences encourage voluntary recommendations when they create emotional closeness between customers and the hotel brand. Managers should therefore design personalized, meaningful, and memorable service experiences to strengthen brand intimacy and support brand evangelism.